OS 09-02 PREVALENCE AND DETERMINANTS OF EXAGGERATED MORNING SURGE AND MORNING HYPERTENSION IN CHINESE: THE CHINA AMBULATORY AND HOME BLOOD PRESSURE REGISTRY (ABPR). (September 2016) - Guo, Qian-Hui; Kang, Yuan-Yuan; Song, Jie; Chen, Qi; Liu, Chang-Yuan; Xu, Shao-Kun; Cheng, Yi-Bang; Li, Yan; Wang, Ji-Guang
Abstract : Objective: Prognosis of exaggerated morning surge (MS) of blood pressure (BP) remains controversial, possibly due to the ethnic difference in the size of MS. Compared to MS, evidence on morning hypertension (MH) is more consistent. With the use of a national BP registry database, we studied the size of MS and the prevalence and determinants of exaggerated MS and MH in Chinese. Design and Method: In the 3547 patients (mean age, 56.8 years; women, 49.1%; hypertension, 79.0%) enrolled in the China Ambulatory and Home BP Registry (ABPR), we performed both 24-h ambulatory and 7-day self-measured home BP monitoring. Exaggerated MS was a sleep-trough MS ≥ 35 mmHg as recommended by the Chinese guidelines. Morning hypertension was a mean BP of at least 135/85 mmHg either self-measured at home in the morning or recorded by ambulatory monitors during 6:00–10:00 (8:00–12:00 for patients from Xinjiang Province). Results: In all registered patients, sleep-trough systolic MS averaged (SD) 20.5 (13.5) mmHg, and 457 (12.9%) had an exaggerated MS. Multivariate regression analysis showed that the size of MS was greater in women (β = 1.26 mmHg; P = 0.02), increased with age (0.04 mmHg, P = 0.03), body-mass index (0.16 mmHg, P = 0.03) and 24-h systolic BP (0.05 mmHg, P = 0.006). Totally, 1796 (50.6%) and 1873 (52.8%) patients had MH on home and ambulatory BP monitoring, respectively. In treated hypertensive patients with office BP < 140/90 mmHg (n = 1230), the corresponding values were 32.6% and 37.5%, respectively. Overall, MH was significantly (P ⩽ 0.01) associated with male sex (standardized OR [95% CI], 1.17 [1.04–1.28]), older age (1.27 [1.18–1.37]), body mass index (1.20 [1.12–1.28]), alcohol intake (1.42 [1.16–1.73]), and home heart rate (1.19 [1.11–1.28]). Conclusions: The size of the sleep-trough MS in Chinese is modest, but similar to that reported in Europeans. However, MH is prevalent in Chinese patients, especially in those with cardiovascular risk factors.